Медіатекст: особливості його функціонування - Прудніков, К. В.; Сергієва, А. В. (ХНУРЕ, 2025)
Media text is an integrative means of mass communication and a dynamic one at that, for it composes the verbal, visual and auditory aspects and influences the molds and determines the public's perception. It is an essential part of journalism, advertising, and social media through which emotions, cognition, and social action are steered. Beyond that, media text doesn't just bring to its reader the news but also brings reality itself by making an enormous influence on politics, economics, and culture. Especially in the digital age, when the speed of news dissemination shapes media text as knowledge and public behavior.
Keywords: медіатекст; media text